Future Teachers Discuss their Readiness to Teach EFL in Ecuador (GIST – Education and Learning Research Journal, 2023)
This work examines Ecuadorian teacher trainees’ self-reported pedagogy. Data gathered in focus groups documents participant’ pedagogy, what they stated they learned about teaching in diverse contexts, and the challenges they anticipate as they prepare to begin careers as English language teachers. A constant comparison method was used to determine and cross-reference emergent themes in the data. Findings suggest a disconnect between the objectives of trainees’ program of study and what future teachers felt they need to have in their toolbox and be ready to implement in their practice.
Keywords: Teacher training; diversity; English language teaching; teacher professional development; Ecuador; qualitative research